Attentional bias towards and away from fearful faces is modulated by developmental amygdala damage. (August 2016) - Pishnamazi, Morteza; Tafakhori, Abbas; Loloee, Sogol; Modabbernia, Amirhossein; Aghamollaii, Vajiheh; Bahrami, Bahador; Winston, Joel S.
Abstract: The amygdala is believed to play a major role in orienting attention towards threat-related stimuli. However, behavioral studies on amygdala-damaged patients have given inconsistent results—variously reporting decreased, persisted, and increased attention towards threat. Here we aimed to characterize the impact of developmental amygdala damage on emotion perception and the nature and time-course of spatial attentional bias towards fearful faces. We investigated SF, a 14-year-old with selective bilateral amygdala damage due to Urbach–Wiethe disease (UWD), and ten healthy controls. Participants completed a fear sensitivity questionnaire, facial expression classification task, and dot-probe task with fearful or neutral faces for spatial cueing. Three cue durations were used to assess the time-course of attentional bias. SF expressed significantly lower fear sensitivity, and showed a selective impairment in classifying fearful facial expressions. Despite this impairment in fear recognition, very brief (100 msec) fearful cues could orient SF's spatial attention. In healthy controls, the attentional bias emerged later and persisted longer. SF's attentional bias was due solely to facilitated engagement to fear, while controls showed the typical phenomenon of difficulty in disengaging from fear. Our study is the first to demonstrate the separable effects of amygdala damage on engagement and disengagement of spatial attention. The findings indicate that multiple mechanisms contribute in biasing attention towards fear, which vary in their timing and dependence on amygdala integrity. It seems that the amygdala is not essential for rapid attention to emotion, but probably has a role in assessment of biological relevance.